Meredith and the Novel - Roberts, Neil. author. aut Link
VIII, 286 p.
Keywords: Meredith is a novelist whom many readers have discovered with excitement, drawn to his radical portrayal of social and personal relations, especially of gender. Neil Robert's book is the first full-length study for ten years, and is the first to examine the novels in the light of modern literary theory, especially the work of Mikhail Bakhtin, showing that Meredith is a writer who engages profoundly with the ideological discourses of his time and is a still not fully discovered precursor of the modernist novel.